Stress echocardiography in valvular heart disease - Hirasawa, Kensuke; Izumo, Masaki; Akashi, Yoshihiro J. (Frontiers in Cardiovascular Medicine, 2023)
Valvular heart disease (VHD) has been a significant health problem, particularly in developed countries, in relation to the aging population. Recent developments in the management of VHD require a more accurate assessment of disease severity to determine the need for transcatheter interventions or open heart surgery. Stress echocardiography is a crucial imaging modality for identifying the underlying pathology of VHD. Optimal administration of exercise or intravenous drugs may reveal hemodynamic abnormalities under stress without posing an invasive risk. Therefore, the implementation of stress echocardiography is recommended for determining interventional indications and risk stratification in mitral regurgitation and aortic stenosis. In addition, recent evidence has accumulated regarding the usefulness of stress echocardiography in various conditions including mitral stenosis, aortic regurgitation, and post-interventional VHD. Here, we summarize the current evidence and future perspectives on stress echocardiography in VHD.